Pengaruh Pengunaan Ponsel Pada Remaja Terhadap Interaksi Sosial: indonesia - gabriel lintang; zhafiraZhafira Nadiya Haya; melintania melintania (CV. ITTC INDONESIA, 2022)
The development of an increasingly sophisticated era in the field of technology in the 21st century has made cellphones inseparable from the means of everyday life. For a student, a cellphone can also be related to daily lifestyle. However, because of these cellphones, it is not uncommon for teenagers to have difficulty interacting with the people around them. The purpose of this study was to determine the effect of cellphones on social interaction in the Communication Sciences department of Tidar University with a sample of 70 people taken using non probability sampling. This study used a quantitative method using the IBM SPSS version 25 application. From the results of this study, it can be concluded that teenagers prefer to interact using cellphones rather than interacting directly.